Library of Congress Classification basic. 2011 - Suja', Balqis (2011)
This is a two-hour presentation to enable support staff group understand the basic structure of LCC, as well as subdivision techniques used throughout LCC, and how to read LCC call number. The lecture ended with individual exercise on how to organize items with LCC call number on the shelf.